Long-Term Persistence of Arbuscular Mycorrhizal Fungi in the Rhizosphere and Bulk Soils of Non-host Brassica napus and Their Networks of Co-occurring Microbes - Floc’h, Jean-Baptiste; Hamel, Chantal; Laterrière, Mario; Tidemann, Breanne; St-Arnaud, Marc; Hijri, Mohamed (Frontiers in Plant Science, 2022)
Arbuscular mycorrhizal fungi (AMF) are obligate plant symbionts that improve the nutrition and health of their host. Most, but not all the crops form a symbiosis with AMF. It is the case for canola (Brassica napus), an important crop in the Canadian Prairies that is known to not form this association. From 2008 to 2018, an experiment was replicated at three locations of the Canadian Prairies and it was used to assess the impact of canola on the community of AMF naturally occurring in three cropping systems, canola monoculture, or canola in two different rotation systems (2-years, canola-wheat and 3-years, barley-pea-canola). We sampled canola rhizosphere and bulk soils to: (i) determine diversity and community structure of AMF, we expected that canola will negatively impact AMF communities in function of its frequency in crop rotations and (ii) wanted to assess how these AMF communities interact with other fungi and bacteria. We detected 49 AMF amplicon sequence variants (ASVs) in canola rhizosphere and bulk soils, confirming the persistence of a diversified AMF community in canola-planted soil, even after 10 years of canola monoculture, which was unexpected considering that canola is among non-mycorrhizal plants. Network analysis revealed a broad range of potential interactions between canola-associated AMF and some fungal and bacterial taxa. We report for the first time that two AMF, Funneliformis mosseae and Rhizophagus iranicus, shared their bacterial cohort almost entirely in bulk soil. Our results suggest the existence of non-species-specific AMF-bacteria or AMF-fungi relationships that could benefit AMF in absence of host plants. The persistence of an AMF community in canola rhizosphere and bulk soils brings a new light on AMF ecology and leads to new perspectives for further studies about AMF and soil microbes interactions and AMF subsistence without mycotrophic host plants.